Genetic Variability, Heritability, and Genotypic Correlation of Soybean Agronomic Characters - Heru Kuswantoro; Moch Muchlish Adie; Pratanti Haksiwi Putri (Buletin Palawija, 2021)
Genetic parameters are important in genetic improvement and variety development. This study aimed to determine the effective characters that can be applied as selection criterion in soybean breeding using genetic parameters. About 100 soybean genotypes were grown in the Muneng Agricultural Technology Research and Assessment Installation from April to July 2020. The trial was conducted using a randomized complete block design. The results showed that high genetic variability was found on days to maturity, number of branches per plant, number of productive nodes per plant, 100-seed weight, and seed yield. The high heritability was shown by days to maturity, plant height, number of branches per plant, and 100-seed weight. All phenotypic correlations were significant, except for the correlation between seed yield and days to maturity, plant height, number of branches, and number of productive nodes. The seed yield had no genotypic correlation with all agronomic characters observed. The genotypic correlation was only significant for plant height and number of productive nodes, number of branches and number of filled pods, as well as number of productive nodes and 100-seed weight. Therefore, the improvement of seed yield can be conducted through direct selection using the seed yield parameter or indirectly using the 100-seed weight.